MAPKinase inhibition after failure of immune checkpoint blockade in patients with advanced melanoma: an evaluation of the multicenter prospective skin cancer registry ADOREG - Kreft, Sophia; Glutsch, Valerie; Zaremba, Anne; Schummer, Patrick; Mohr, Peter; Grimmelmann, Imke; Gutzmer, Ralf; Meier, Friedegund; Pföhler, Claudia; Sachse, Michael Max; Meiß, Frank; Forschner, Andrea; et al. (European journal of cancer, 2022)
Objectives - Forty to sixty percent of patients with advanced melanoma show primary resistance to PD-1-based immunotherapy, 30-40% of initial responders also progress. Here, we evaluated the outcome of second-line targeted therapy (TT) after progression on PD-1-based immune checkpoint inhibition (ICI) in BRAFV600-mutated melanoma. In addition, we report data on the activity of re-exposure with PD-1-based regimes. - Methods - Patients with advanced (non-resectable stage III or IV, AJCC 2017, 8th edition) melanoma progressing on PD-1-based ICI (nivolumab, pembrolizumab or ipilimumab plus nivolumab) and receiving second-line BRAF plus MEK inhibition were identified from the prospective multicenter skin cancer registry ADOREG. - Results - We identified 108 patients with unresectable stage III or stage IV melanoma progressing on first-line ICI (nivolumab, pembrolizumab or ipilimumab plus nivolumab) and receiving second-line combined BRAF/MEK inhibition. Seventy-three percent of the cohort presented with primary PD-1 resistant disease. Median progression-free survival (PFS) on ICI was 2.6 (95% CI 2.2-2.9) months. Median PFS on subsequent TT was 6.6 (95% CI 5.4-7.8) months. Median OS from start of second-line TT was 16.0 (95% CI 11.2-20.8) months. The 3-year PFS and OS rates on second-line TT were 16% and 30%. The objective response rate (ORR) and disease control rate (DCR) to TT were 42.6% and 55.6%. In patients with brain metastases, the ORR and DCR were 31.4% and 43.1%. Patients without brain metastases showed an ORR and DCR of 52.6% and 66.7%, respectively. Response to first-line ICI was associated with a numerically higher ORR and DCR to second-line TT and improved OS on TT. Twenty-three patients received third-line ICI of whom two patients showed an objective response. - Conclusions - BRAF plus MEK inhibition shows meaningful activity and outcome in patients with advanced melanoma resistant to anti-PD-1-based immunotherapy. Rates of long-term benefit and survival in our study were similar to those reported for treatment-naïve patients receiving first-line MAPKi.
Online verfügbar: 30. März 2022, Artikelversion: 30. März 2022
Gesehen am 16.09.2024